Re-conceptualizing gangmastering and labour exploitation: From the interpersonal dimension of victim-perpetrator to the “labour control regime”: Rethinking enforcement instruments (Sociologia del diritto, 2024)
This paper argues for a reconceptualisation of gangmastering and labour exploitation that differs from the dominant narrative inspired by the “modern slavery” paradigm, which narrows the focus on the intersubjective victim-perpetrator relationship of domination. In order to explore the complexity inherent in the labour practices and relations under analysis, the paper suggests that the concept of “labour control regime” (LCR) would be far more effective than the current narrative, as it is capable of shifting the focus to a broader notion of coercion. Such a perspective suggests that we consider a plurality of actors and processes that contribute to the production and reproduction of the conditions for the proliferation of the phenomena under consideration, and thus to rethink the instruments of counteraction put in place so far.
Keywords: gangmastering; modern slavery; migrant labour; “labour control regime”; informalisation of labour; labour force devaluation